Reading approach to improve strength: an explorative study - Lovecchio, N. (Journal of Human Sport & Exercise, 2016)
Many studies and common practice use different load and recovery time combinations to obtain improvements in strength performance. The cross education and speech neurons theory could lead to new strategies in motor skills learning and in fitness improvement. Thus, the aim of this study was to verify if a process similar to cross education and visual phenomenon (reading approach) could improve the strength performance.